Efficacy and safety of platelet-rich plasma for acute nonarteritic anterior ischemic optic neuropathy: a prospective cohort study - Jin, Xin; Fu, Junxia; Lv, Ruju; Hao, Xiaolu; Wang, Song; Sun, Mingming; Xu, Guangcan; Zhang, Qi; Zhang, Lei; Li, Yan; Xu, Quangang; Hou, Baoke (Frontiers in Medicine, 2024)
Background: As the most common acute optic neuropathy in older patients, nonarteritic anterior ischemic optic neuropathy (NAION) presents with varying degrees of visual acuity loss and visual field defect. However, there is no generally accepted treatment for NAION.To evaluate the efficacy and safety of platelet-rich plasma (PRP) for patients with acute NAION within 2 months.Design: A prospective, nonrandomized controlled trial.Methods: Twenty-five eyes of 25 patients were enrolled. Of them, 13 received anisodine hydrobromide and butylphthalide-sodium chloride injection continuously for 10 days as basic treatment in the control group, and 12 received two tenon capsule injections of PRP on a 10-day interval as an additional treatment in the PRP group.We compared the best-corrected visual acuity (BCVA) and capillary perfusion density (CPD) of radial peripapillary capillaries and the moth-eaten eara of the peripapillary superficial capillary plexus and deep capillary plexus at 1 day (D1) before the first PRP treatment and 7 days (D7), 14 days (D14), and 30 days (D30) after the first PRP injection. Ocular and systemic adverse effects were assessed.In the PRP group, a better BCVA occurred at D30 (adjusted P=0.005, compared with D1, recovered from 0.67±0.59 to 0.43±0.59), and a significant improvement in CPD was observed at D30 (adjusted P<0.001, P=0.027, P=0.027, compared with D1, D7, D14, in sequence, the value was 35. 97±4.65, 38.73±4.61, 39.05±5.26, 42.71±4.72, respectively). CPD at D7 in the PRP group was better than that in the control group (P=0.043). However, neither BCVA nor the moth-eaten area index were significantly different (all P>0.5) between the two groups. The main adverse effect was local discomfort resolved within 1 week, and no other systemic 3 adverse events occurred.Tenon capsule injection of PRP was a safe treatment for AION and could improve capillary perfusion of the optic nerve head and might be helpful in increasing short-term vision in patients with acute NAION.